2021
DOI: 10.47440/jafe.2021.2305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc on growth and yield of rice cv. BRRI dhan29 under alternate wetting and drying water management practice

Abstract: Insufficient zinc (Zn) and water are key concerns in agricultural production, resulting in lower yields and nutritional qualities. The goal of the study was to figure out how water management and Zn application rates affect the growth and yield of rice. The experiment was carried out in a split-plot design with three replications. The treatments consisted of two factors, a) water management, like 1) Continuous flooding (CF) and 2) Alternate wetting and drying (AWD) system and b) Zn application like 1) Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…increase in grain weight upon zinc fertilization could be attributed to enhanced zinc uptake and translocation of sugars and higher carbohydrate accumulation in seed. Similar results have been reported by Kumar et al (2017) and Farzana et al (2021). The interaction effect indicated that the maximum 1000-seed weight (27.43 g) was with interaction of BRRI hybrid dhan5 with 6 kg Zn ha -1 .…”
Section: Variety × Zn Level Number Of Panicles Hillsupporting
confidence: 89%
See 3 more Smart Citations
“…increase in grain weight upon zinc fertilization could be attributed to enhanced zinc uptake and translocation of sugars and higher carbohydrate accumulation in seed. Similar results have been reported by Kumar et al (2017) and Farzana et al (2021). The interaction effect indicated that the maximum 1000-seed weight (27.43 g) was with interaction of BRRI hybrid dhan5 with 6 kg Zn ha -1 .…”
Section: Variety × Zn Level Number Of Panicles Hillsupporting
confidence: 89%
“…Among the rate of Zn application, the longest panicle (27.14 cm) was recorded in 6 kg Zn ha -1 and the shortest panicle (24.78 cm) obtained from 0 kg Zn ha -1 treatment. A similar kind of result was also reported by Farzana et al (2021) in which the adequate supply of zinc results in the greater panicle length. The interaction effect of different rate of variety and zinc in hybrid rice, the longest panicle (29.45 cm) was recorded in BRRI hybrid dhan5 along with 6 kg Zn ha -1 treatment combination.…”
Section: Panicle Lengthsupporting
confidence: 85%
See 2 more Smart Citations
“…The increase was higher in low-Zn-containing soils than high-Zn-containing soils. The application of Zn to soil exhibited approximately a 10% increase in dry shoot biomass compared to when no Zn was applied to soil [29]. Naik and Das [30] reported that the application of Zn to low land rice soil resulted in the 37.8% and 20.9%, the most significant increase in the grain and straw yield of rice, respectively, over the control.…”
Section: Discussionmentioning
confidence: 99%